Mechanism of bidirectional thermotaxis in Escherichia coli - Paulick, Anja; Jakovljević, Vladimir; Sourjik, Victor (eLife, 2017)
The interplay between the opposing responses mediated by different chemoreceptors enables bacteria to swim towards a preferred temperature.